2021
DOI: 10.1364/oe.446192
|View full text |Cite
|
Sign up to set email alerts
|

Collisional mixing and quenching cross sections of Cs 62P levels with methane, ethane, and propane

Abstract: Mixing cross sections of Cs between the 62P1/2 and 62P3/2 levels and quenching cross sections from these levels to the ground state 62S1/2 were measured, with methane, ethane, and propane as collision partners. We excited Cs to the 6P3/2 level with a tunable nanosecond pulse laser and measured the fluorescence at the 62P1/2 level. The measured mixing cross sections with methane, ethane, and propane were (1.39 ± 0.16), (5.67 ± 0.85), and (7.91 ± 0.93)×10−15 cm2, respectively, and the statistically averaged quen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…However, there are surprisingly few reports on the collisional mixing reaction cross sections of Cs and these hydrocarbons, as well as the quenching reaction cross sections associated with the collisions. Therefore, Endo et al measured and reported a total of six reaction cross sections for the mixing and quenching of Cs with methane, ethane, and propane [14]. The results for methane were comparable to previous high-precision measurements [15], while the quenching cross section for propane was reported for the first time.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…However, there are surprisingly few reports on the collisional mixing reaction cross sections of Cs and these hydrocarbons, as well as the quenching reaction cross sections associated with the collisions. Therefore, Endo et al measured and reported a total of six reaction cross sections for the mixing and quenching of Cs with methane, ethane, and propane [14]. The results for methane were comparable to previous high-precision measurements [15], while the quenching cross section for propane was reported for the first time.…”
Section: Introductionsupporting
confidence: 57%
“…The mixing and quenching reaction cross sections are the main trend determinants. In the present calculations, these have been set to our measured values [14]. The validity of the measured cross sections was confirmed by the fact that the numerical simulation based on them effectively reproduced the experimental results.…”
Section: Comparison Of the Experimental Results With Calculationsmentioning
confidence: 54%
See 2 more Smart Citations